1998
DOI: 10.1038/31014
|View full text |Cite
|
Sign up to set email alerts
|

A cytokinesis checkpoint requiring the yeast homologue of an APC-binding protein

Abstract: Checkpoint controls ensure that events of the cell-division cycle are completed with fidelity and in the correct order. In budding yeast with a mutation in the motor protein dynein, the mitotic spindle is often misaligned and therefore slow to enter the neck between mother cell and budding daughter cell. When this occurs, cytokinesis (division of the cytoplasm into two) is delayed until the spindle is properly positioned. Here we describe mutations that abolish this delay, indicating the existence of a new che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 16 publications
3
108
0
2
Order By: Relevance
“…The checkpoint is essential for the viability of mutant cells lacking components of the dynein-dynactin complex, which have defects in spindle positioning. Therefore, inactivation of genes encoding components of this checkpoint is lethal in cells lacking dynein (65). Indeed, a partial loss of function mutation in STT4 is lethal in dynactin complex mutants (65), suggesting that the PI 4-kinase encoded by STT4 is required for checkpoint function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The checkpoint is essential for the viability of mutant cells lacking components of the dynein-dynactin complex, which have defects in spindle positioning. Therefore, inactivation of genes encoding components of this checkpoint is lethal in cells lacking dynein (65). Indeed, a partial loss of function mutation in STT4 is lethal in dynactin complex mutants (65), suggesting that the PI 4-kinase encoded by STT4 is required for checkpoint function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inactivation of genes encoding components of this checkpoint is lethal in cells lacking dynein (65). Indeed, a partial loss of function mutation in STT4 is lethal in dynactin complex mutants (65), suggesting that the PI 4-kinase encoded by STT4 is required for checkpoint function. However, an alternative explanation is that a spindle-positioning defect is lethal in combination with a defect in mitotic exit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal domain of APC binds to microtubules as well as to a protein called EB1. It has been shown that the EB1 protein associates at the spindle microtubules and centrosomes, and functions in the cytokinesis checkpoint (Muhua et al, 1998). Recently, APC was also suggested to play a role in kinetochore-microtubule attachment, whereas truncated mutations of APC, which eliminate microtubule binding, induce chromosomal missegregation and the CIN phenotype (Kaplan et al, 2001;Fodde et al, 2001).…”
Section: Numerical Cin and Its Potential Causesmentioning
confidence: 99%
“…During G1, microtubules in cells lacking BIM1p showed reduced dynamicity due to a slower shrinkage rate, fewer rescues and catastrophies, and more time spent in an attenuated/paused state (Tirnauer et al, 1999). A delay in the cell cycle before cytokinesis in cells with mutated EB1/RP1 homologues was observed in budding yeast as well (Muhua et al, 1998). At least in yeast, homologues of the human EB/RP protein family may be a necessary component of a new cellcycle checkpoint.…”
Section: Introductionmentioning
confidence: 93%